1991
DOI: 10.1111/j.1471-4159.1991.tb03776.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Enhances Striatal Dopaminergic Parameters in the 1‐Methyl‐4‐Phenyl‐l, 2, 3, 6‐Tetrahydropyridine‐Treated Mouse

Abstract: Intracerebroventricular infusion of epidermal growth factor (EGF) into mice with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced degeneration of dopaminergic nigrostriatal neurons partially enhanced the content of dopamine (DA) and 3,4-dihydroxyphenylacetic acid as well as the activity of tyrosine hydroxylase in the striatum. EGF also enhanced these parameters in control, unlesioned animals. Neurotrophic activity also was observed in embryonic mesencephalic cultures, where EGF enhanced DA uptake af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Significantly, TGF-␣ mutant mice exhibit significant reductions in SNc DA neurons (19). Furthermore, EGF and EGFR protein levels are significantly decreased in the striatum of PD patients (2), and EGF treatment has been shown to protect DA neurons in primary VM cultures and animal models of PD (2,4,(26)(27)(28). Familial PD can be caused by mutant dysfunctional parkin (PARK2 in PD gene classification), and normal parkin (29,30) can delay EGFR internalization and degradation and promote PI3-K/Akt signaling (31).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, TGF-␣ mutant mice exhibit significant reductions in SNc DA neurons (19). Furthermore, EGF and EGFR protein levels are significantly decreased in the striatum of PD patients (2), and EGF treatment has been shown to protect DA neurons in primary VM cultures and animal models of PD (2,4,(26)(27)(28). Familial PD can be caused by mutant dysfunctional parkin (PARK2 in PD gene classification), and normal parkin (29,30) can delay EGFR internalization and degradation and promote PI3-K/Akt signaling (31).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of 6-OHDA (SOD), by scavenging superoxide radicals, dramatically inon both the central and peripheral catecholaminergic pathways hibits the oxidation of 6-OHDA (39). Subsequent studies in rodents and in a variety of cultured cell types have been re-have confirmed the production of superoxide radicals, and viewed elsewhere, as well as the molecular basis for its speci-have moreover demonstrated that superoxide radicals generficity (45,46,65). 6-OHDA can be administered to rodents via ated by the first step of 6-OHDA oxidation are critical in a variety of different routes, but its proper utilization in vivo propagating the oxidation of 6-OHDA (11,30,31,80 This shows that the oxidation of 2 moles of 6-OHDA leads to THE HERBICIDE PARAQUAT the formation of 2 moles of quinone and 2 moles of H,0 2 .…”
Section: Still In the Racementioning
confidence: 99%
“…PRZEDBORSKI AND ISCHIROPOULOS the pathogenesis of the disease have emerged from studies and in vitro relies on one's knowledge of a series of technical probing the functions of genes implicated in inherited forms points that have been discussed in detail (45,46,65). Because of PD and from animal and cellular model systems of PD.…”
mentioning
confidence: 99%
“…De hecho, se demostró que actúa como un factor neurotrófico sobre neuronas cultivadas de la corteza cerebral, del telencéfalo subneocortical y del cerebelo, incrementando el crecimiento neurona1 y la supervivencia (5-7). Su acción neurotrófica sobre las neuronas dopaminérgicas se describió como un incremento de la supervivencia y de la maduración (8,9).…”
unclassified